2007
DOI: 10.1007/s10488-006-0108-5
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship of Antipsychotic Medication Class and Adherence with Treatment Outcomes and Costs for Florida Medicaid Beneficiaries with Schizophrenia

Abstract: While some studies show a significant advantage in adherence rates with use of atypical versus typical antipsychotic medication, others show no advantage or mixed results (Jones et al. (2006). Archives of General Psychiatry, 63, 1079-1087; Rosenheck, (2006). Archives of General Psychiatry, 63, 1074-1076). This study examined treatment outcomes and costs associated with adherence rates by antipsychotic medication class for adult Medicaid beneficiaries in Florida diagnosed with schizophrenia. Outcomes examined i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 44 publications
1
29
0
1
Order By: Relevance
“…Patients assigned to clozapine were 63% less likely to discontinue than those on LAIR (Hazard Ratio (HR) = .37), while those on olanzapine, risperidone or quetiapine were 17-22% less likely to discontinue (HR = .78-.83) than those on LAIR. [17], to be identified as African American [9,18,19], to be dually diagnosed with alcohol or drug abuse, and to be more severely ill as indicated by a greater likelihood of inpatient psychiatric hospitalization in the previous year and a greater number of outpatient mental health visits [9]. Tellingly, these are all characteristics commonly associated with poor medication compliance [20].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients assigned to clozapine were 63% less likely to discontinue than those on LAIR (Hazard Ratio (HR) = .37), while those on olanzapine, risperidone or quetiapine were 17-22% less likely to discontinue (HR = .78-.83) than those on LAIR. [17], to be identified as African American [9,18,19], to be dually diagnosed with alcohol or drug abuse, and to be more severely ill as indicated by a greater likelihood of inpatient psychiatric hospitalization in the previous year and a greater number of outpatient mental health visits [9]. Tellingly, these are all characteristics commonly associated with poor medication compliance [20].…”
Section: Resultsmentioning
confidence: 99%
“…It was initially believed that reduced risk of neurological side effects with second generation antipsychotic medications (SGAs)--currently including clozapine, risperidone, olanzapine, quetiapine, ziprasidone and aripiprazole--would enhance tolerability, increase adherence and thereby improve outcomes [9]. Although some subsequent studies of oral medication have not confirmed these findings [10][11][12][13], the introduction of long-acting injectable risperidone (LAIR) (Risperdal Consta Ò ), in 2003, renewed hope that the combination of long-acting formulation with a second generation antipsychotic might offer distinct advantages in the treatment of schizophrenia [4,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…However, many prior reports were significantly limited because they were conducted with predominantly Euro-American populations. Ethnic and racial disparities in adherence have been noted, with prior studies finding that non-white patients were more likely to have lower adherence (3, 2123). …”
Section: Introductionmentioning
confidence: 97%
“…La falta de adherencia al tratamiento farmacológi-co en la esquizofrenia se asocia a un mayor deterioro global, secundario a un mayor número de recaídas, exacerbación de síntomas psicóticos y mayor número de hospitalizaciones psiquiátricas a lo largo del padecimiento. 12,26,[43][44][45][46] La falta de adherencia al tratamiento no sólo impacta en el manejo de la enfermedad; un mayor número de hospitalizaciones implica mayores costos para el paciente y sus familiares en la atención especializada, así como un mayor uso de recursos del sistema de salud en términos del empleo de instalaciones hospitalarias y de más medicamentos concomitantes. [47][48][49][50] En el manejo de la esquizofrenia no sólo es importante considerar la eficacia de un medicamento en el control de los síntomas psicóticos.…”
Section: Discussionunclassified